Effect of nutritional intervention combined with vitamin D on glucose metabolism, sex hormones and inflammatory factors in patients with Polycystic ovary syndrome: Impact of nutritional interventions on PCOS - Kang, Xinqin; Liu, Lin (Journal of Medical Biochemistry, 2025)
Backgrounds: Polycystic ovary syndrome is a very common endocrine and metabolic disease in clinical practice. Most polycystic ovary syndrome patients are complicated with obesity, a condition associated with an elevated risk of long-term complications such as diabetes, hypertension, and endometrial cancer, seriously threatening the health of patients. The best way to treat this disease is to use drugs to promote ovulation, adjust the menstrual period, and restore pregnancy. However, the drugs used to treat obesity and polycystic ovary syndrome usually have completely opposite effects, resulting in unsatisfactory rehabilitation. Methods: This study selected 102 obese PCOS patients treated in our hospital from July 2022 to July 2024 as the research subjects. Sex hormones: The levels of prolactin (PRL), testosterone (T), follicle-stimulating hormone (FSH), and luteinizing hormone (LH) were measured by electrochemiluminescence. Inflammation: C-reactive protein (CRP), white blood cell count (WBC), and procalcitonin (PCT) were examined by an automated blood cell counter. 46 (control group) of the 102 were treated with conventional treatment scheme, and the other 46 (experimental group) were intervened by nutritional intervention based on conventional treatment. Results: Both groups showed reductions in sex hormone levels after treatment, with the PRL, T, LH, and FSH in the experimental group being (5.12±0.51)mIU/mL, (1.22±0.32)nmol/L, (9.14±1.61)IU/L, and (5.01±0.42)IU/L, respectively, all of which were lower compared with the control group (P<0.05). Conclusion: In this study, we intervened obese polycystic ovary syndrome patients with nutritional or conventional intervention and found that compared with conventional treatment, the posture, blood glucose metabolism, and lipid function of the patients who received nutritional intervention were more significantly metabolized, and the levels of inflammatory factors were more effectively inhibited, indicating the high clinical application value of nutritional intervention in obese polycystic ovary syndrome.